AB0248 Circulating Cell Free DNA; A Marker To Predict The Therapeutic Response for Biological Dmards in Rheumatoid Arthritis. (15th July 2016) - Hasimoto, T.; Yoshida, K.; Hashimoto, N.; Kaneshiro, K.; Nakai, A.; Kawasaki, Y.; Hashiramoto, A.
Abstract : Background: DNA is fragmented and released into blood circulation as results of damage or death of cells from peripheral bloods as well as organ tissues, and circulating cell-free DNA (ccfDNA) has been recognized as biomarkers of several medical conditions [1]. In patients with rheumatoid arthritis (RA), serum concentration of ccfDNA has been reported to be elevated [2], however, the relation between ccfDNA and the pathogenesis of RA remains unclear. Objectives: To evaluate the correlation between ccfDNA in plasma and clinical disease activities in patients with RA. Methods: The study group included 29 patients with RA who started biological DMARDs therapy. The concentration of ccfDNA in plasma was measured by quantitative real-time PCR at baseline to 24 weeks in every 4 weeks-period from 29 patients, and 21 healthy individuals. We also evaluated the correlation between ccfDNA and the clinical activities or the response for biological DMARDs, using disease activity score of 28 joints erythrocyte sedimentation rate (DAS28ESR) and the european league against rheumatism (EULAR) response criteria. In addition, synovial fluid samples of knee joint were collected from 14 patients with RA and12 with osteoarthritis (OA) to measure ccfDNA Results: The concentration of ccfDNA in RA patients at baseline was higher than healthy controls (p=0.016).When evaluated the concentration of ccfDNA, it was increased until 8 weeks-period from the baseline, and then decreased after 12weeks-period. The average of DAS28ESR was improved in all patients enrolled. At 12weeks-period after treatment, 15 patients were good responders of the EULAR response criteria, 9 showed the moderate response and 5 showed no response. The concentration of ccfDNA in good responder was increased until 8weeks while those of moderate or no responder were not (P=0.042) (figure ), and there was no significant difference between ccfDNA at baseline and other parameters in all patients. In joint fluid of RA patients, the concentration of ccfDNA was remarkably increased as compared to those from OA (P=0.00011). Conclusions: Increase of ccfDNA at 8 weeks-period was associated with improvement of disease activity. Compared with the biomarkers reported before, ccfDNA is possible to predict the early therapeutic effects of biological DMARDs in RA patients. References: Jiajia Y, Guohao G, Shaoqing J. Recent Advances in Clinical Applications of Circulating Cell-free DNA Integrity. Lab medicine 2014;45:6–12 Zhong XY, Muhlenen IV, Li Y, Kang A, Gupta AK, Tyndall A, et al. Increased Concentrations of Antibody-Bound circulatory cell-free DNA in rheumatoid arthritis. Clin Chem 2007;53:1609–1614 Disclosure of Interest: None declared